Analisis Sosiodemografi terhadap Pemberian ASI Eksklusif di Provinsi Sulawesi Selatan : Analisis Data Susenas 2017 - Ayulestari, Dwi; Soewondo, Prastuti (Media Kesehatan Masyarakat Indonesia, 2019)
Breastfeeding is one of mother’s responsibility to give children’s need of nutrition for healthy growth and development. This research using secondary data from National Social Economic Survey 2017. The respondents was all mother with 6-24 month baby in South Sulawesi Province as many as 1.857 mothers. Binary regression with Logit Models and Probit Models was used to uncover the probability from factor sosiodemography to exclusive breastfeeding. The result showed that mother’s age negatively related to exclusive breastfeeding with coefficient Logit value -0,105 and Probit value -0,600 (p value < 0,01). The result also found that household income positively related to exclusive breastfeeding with coefficient Logit value 0,645 and Probit value 0,376 (p value <0,01), the same with parity which positively related with coefficient Logit value 1,210 and Probit value 0,713 (p value <0,01). Mother’s age was the factor sociodemography to exclusive breastfeeding, however mother’s age showed negative effect. Moreover, respondents with household income and parity showed positive effect with exclusive breastfeeding. This conclude that the higher mother’s age, the higher chance of mother to not giving exclusive breastfeeding.